Traditional Games as a Multicultural Education Planning for Children in Primary Schools - Freddy Widya Ariesta; Bunyamin Maftuh (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2020)
This study aims to examine the planting of values of multicultural education in children in Primary Schools through traditional games. This is motivated by the diversity of cultures, races, languages, and religions in Indonesia. Traditional children's games or called “Dolanan Anak” is one of the nation's cultural assets that must be preserved. Traditional games not only provide value for recreation or pleasure. More than that, traditional games also contain and contain elements of cultural values that are identical to multicultural education. These values are cultural heritage, which is full of the meaning of goodness and is useful in developing community life in children. This article is a study of the research literature that describes traditional games as an attempt to integrate the values of multicultural education. This importance is given to children or students of Primary Schools age in the hope that the children can understand early on that the diversity of national cultures is a vehicle to foster tolerance and respect in their living environment and the external environment that has a diversity of cultures.